ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA PECAHAN DAN PENYEBABNYA - Martha Mila Sughesti; Gatot Muhsetyo; Hery Susanto (Jurnal Kajian Pembelajaran Matematika, 2020)
The facts show that there are still many students who make mistakes in solving fraction story questions. The research objective was to identify and analyze student errors in solving fraction story questions. This type of research is a qualitative descriptive study. The research subjects were three grade VII junior high school students who were all girls. Subjects were given two tests of fraction story questions. This research was started from August 2016 to January 2017. The test answer sheets were identified, then analyzed. The results showed that almost all the errors of Newman procedure were carried out by the subject, namely: (1) reading (2) understanding (3) transformation errors (4) skills skills and (5) layout and different intensity of errors for each subject. Causes: (1) reduced verbal ability (2) low algorithmic ability (3) error prerequisite material (4) accuracy (5) lack of desire to solve questions.Keywords: story problem, fraction, Newman procedure